2010
DOI: 10.1590/s1679-45082010ao1592
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of radical prostatectomy techniques using perineal or suprapubic approach in the treatment of localized prostate cancer

Abstract: Objective: To compare the results of radical prostatectomy by perineal and suprapubic approaches as to operative time, procedure costs, and surgical site complications. Methods: The medical records of localized prostate cancer patients (PSA ≤ 10 ng/ml and Gleason score ≤ 6) were analyzed. Fifty-five patients were submitted to radical prostatectomy by perineal approach and 54 via suprapubic approach. results: There were statistical differences between groups as to operative time (p < 0.05); for perineal approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…They reported no difference in rectal injury between RRP and open RPP techniques. Amorim et al [24] reported that rectal injury in 2.2-2.8% of laparoscopic extraperitoneal RP operations. Tewari et al [25] reported the risk of rectal injury as 0.5-1.5% in robot-assisted laparoscopic RP operations.…”
Section: Discussionmentioning
confidence: 99%
“…They reported no difference in rectal injury between RRP and open RPP techniques. Amorim et al [24] reported that rectal injury in 2.2-2.8% of laparoscopic extraperitoneal RP operations. Tewari et al [25] reported the risk of rectal injury as 0.5-1.5% in robot-assisted laparoscopic RP operations.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other methods, this technique is performed with an instrument manoeuvre capability of 540 degrees under the high-resolution image of robotic system at a different compartment in a narrow area. However, there may be some factors that can be considered as limitations of this technique such as different pelvimetric measurements (7)(8)(9). No rectal injury was observed in our series of R-PRP.…”
Section: Discussionmentioning
confidence: 75%
“…Radical prostatectomy (RP) is not free of complications, since intraoperative blood loss, lymphocele, infection, postoperative urinary incontinence, reoperation and erectile dysfunction may occur 3 - 4 . The suprapubic prostatectomy has an average duration of 02:47 hours 5 .…”
Section: Introductionmentioning
confidence: 99%